2016
DOI: 10.1002/anie.201603177
|View full text |Cite
|
Sign up to set email alerts
|

The Radical Anion and Dianion of Tetraazapentacene

Abstract: The mono- and bis-reduction of 6,13-bis((triisopropylsilyl)ethynyl)quinoxalino[2,3-b]phenazine (1) with potassium anthracenide in THF is reported. Both the radical anion 1(.-) and the dianion 1(2-) were isolated and characterized by optical and structural (single-crystal X-ray diffraction) methods. Solutions of the radical anion 1(.-) were stable in air for several hours and characterized by EPR spectroscopy. Dianion 1(2-) is highly fluorescent and photostable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
33
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 29 publications
9
33
0
2
Order By: Relevance
“…We grew single crystals of 1C À suitable for X-ray-structure analysis (Figures 4a nd 5). As in previously reported radical anions of azaacenes, [14] the potassium cation does not show any interaction with the negatively charged azaacene.Asthe charge is distributed over the large p system, the radical anion lacks the hard Lewis-basic properties needed to coordinate to the potassium cation in the presence of THF.T he packing of 1C À K + is shown in the middle and bottom parts of Figure 4. The( 18-crown-6)(THF) 2 -coordinated potassium ions are located between the large p systems,a nd the cations and anions do not interact strongly.F igure 5s hows the minute changes in bond lengths when going from 1 to its radical anion, which are mostly less than 0.02 .T he bond length alternation in the eastern and western rings of 1C À is not as pronounced as in the structure of 1.…”
Section: Angewandte Chemiesupporting
confidence: 84%
See 2 more Smart Citations
“…We grew single crystals of 1C À suitable for X-ray-structure analysis (Figures 4a nd 5). As in previously reported radical anions of azaacenes, [14] the potassium cation does not show any interaction with the negatively charged azaacene.Asthe charge is distributed over the large p system, the radical anion lacks the hard Lewis-basic properties needed to coordinate to the potassium cation in the presence of THF.T he packing of 1C À K + is shown in the middle and bottom parts of Figure 4. The( 18-crown-6)(THF) 2 -coordinated potassium ions are located between the large p systems,a nd the cations and anions do not interact strongly.F igure 5s hows the minute changes in bond lengths when going from 1 to its radical anion, which are mostly less than 0.02 .T he bond length alternation in the eastern and western rings of 1C À is not as pronounced as in the structure of 1.…”
Section: Angewandte Chemiesupporting
confidence: 84%
“…(1), and thiadiazolo [3,4-b] Theelectron affinities were calculated at the DFT/CAM-B3LYP level to be 4.03 eV for the parent TIPSTAP and 4.33 eV for 1,t hus making 1 attractive for n-channel semiconductors.T he first reduction potential of 1 is remarkably low (À0.7 Vv ersus ferrocene), which suggested that the radical anion might be stable in air. [14] Thedianion has the most blue-shifted absorption spectrum and its solution in Et 2 Oi ss omewhat fluorescent (quantum yield 3.5 %), despite the presence of the four bromine atoms,which would be expected to facilitate intersystem crossing through the heavy-atom effect. Figure 2s hows the absorption spectra of the neutral compound, the radical anion, and the dianion of 1.Asinthe case of TIPSTAP,t he spectrum of the radical anion is redshifted the most, followed by that of neutral 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Das erste Reduktionspotential von 1 ist ungewçhnlich niedrig (À0.7 Vg egen Ferrocen) und legt nahe,d ass das Radikalanion von 1 luftstabil sein kçnnte. [13] Um diese Hypothese zu testen, stellten wir eine Lçsung [14] Das Dianion zeigt das kurzwelligste Absorptionsspektrum und fluoresziert in Et 2 O( Quantenausbeute 3.5 %) trotz Anwesenheit der vier Bromsubstituenten, von denen man erwarten würde,d ass sie die strahlungslose Deaktivierung durch Intersystem-Crossing aufgrund des Schweratomeffektes begünstigten. Die geringe Stokes-Verschiebung zeigt den p-p*-Charakter des S 0 -S 1 -Überganges, und, dass es sich bei der Emission um Fluoreszenz handelt, welches ebenfalls durch die Emissionslebenszeiten (t 1 < 1ns (26 %), t 2 = 2.0 ns (22 %), t 3 = 4.5 ns (52 %)) belegt ist.…”
unclassified
“…Zur Strukturanalyse wurden geeignete Einkristalle von 1C À erhalten (Abbildungen 4u nd 5). Wiei nd en zuvor verçffentlichten Strukturen von Azaacen-Radikalanionen [14] zeigt das Kaliumkation keine Wechselwirkung mit dem negativ geladenen Azaacen. Da die negative Ladung über das große p-System delokalisiert ist, fehlt dem Anion die harte Lewis-Basizität, welche nçtig wäre,umdas an das THF koordinierte Kaliumion zu koordinieren.…”
unclassified